Doughty-electronegative heteroatom-induced defective MoS2 for the hydrogen evolution reaction - Xiao, Zhaohui; Luo, Shengdao; Duan, Wei; Zhang, Xu; Han, Shixing; Liu, Yipu; Yang, Liang; Lin, Shiwei (Frontiers in Chemistry, 2022)
Producing hydrogen through water electrolysis is one of the most promising green energy storage and conversion technologies for the long-term development of energy-related hydrogen technologies. MoS2 is a very promising electrocatalyst which may replace precious metal catalysts for the hydrogen evolution reaction (HER). In this work, doughty-electronegative heteroatom defects (halogen atoms such as chlorine, fluorine, and nitrogen) were successfully introduced in MoS2 by using a large-scale, green, and simple ball milling strategy to alter its electronic structure. The physicochemical properties (morphology, crystallization, chemical composition, and electronic structure) of the doughty-electronegative heteroatom-induced defective MoS2 (N/Cl-MoS2) were identified using SEM, TEM, Raman, XRD, and XPS. Furthermore, compared with bulk pristine MoS2, the HER activity of N/Cl-MoS2 significantly increased from 442 mV to 280 mV at a current of 10 mA cm−2. Ball milling not only effectively reduced the size of the catalyst material, but also exposed more active sites. More importantly, the introduced doughty-electronegative heteroatom optimized the electronic structure of the catalyst. Therefore, the doughty-electronegative heteroatom induced by mechanical ball milling provides a useful reference for the large-scale production of green, efficient, and low-cost catalyst materials.